Segmental chromosomal aberrations as the poor prognostic factor in children over 18 months with stage 3 neuroblastoma without MYCN amplification - Wieczorek, Aleksandra; Szewczyk, Katarzyna; Klekawka, Tomasz; Stefanowicz, Joanna; Ussowicz, Marek; Drabik, Grazyna; Pawinska-Wasikowska, Katarzyna; Balwierz, Walentyna (Frontiers in Oncology, 2023)
Introduction: Patients with stage 3 neuroblastoma (NBL) according to International Neuroblastoma Staging Criteria (INSS) without MYCN amplification represent a heterogenous group with respect to disease presentation and prognosis. Methods: Retrospective analysis of 40 stage 3 patients with NBL without MYCN amplification was performed. The prognostic value of age at diagnosis (under 18 vs over 18 months), International Neuroblastoma Pathology Classification (INPC) diagnostic category and presence of segmental or numerical chromosomes aberrations were evaluated, as well as biochemical markers. Array comparative genomic hybridization (aCGH) for analyzing copy number variations and Sanger sequencing for ALK point mutations were done. Results: In 12 patients (two patients under 18 months), segmental chromosomal aberrations (SCA) were found and numerical chromosomal aberrations (NCA) were found in 16 patients (14 patients under 18 months). In children over 18 months SCA were more common (p=0.0001). Unfavorable pathology was significantly correlated with SCA genomic profile (p=0.04) and age over 18 months (p=0.008). No therapy failures occurred in children with NCA profile over or under 18 months or in children under 18 months, irrespective of pathology and CGH results. Three treatment failures occurred in the SCA group, in one patient CGH profile was not available. For the whole group at 3 and 5, and 10-year OS and DFS were 0.95, 0.91 and 0.91, and 0.95, 0.92 and 0.86, respectively. DFS was significantly lower in the SCA group than in NCA group (3-years, 5-years, and 10-years PFS 0.92, 0.8 and 0.6 vs 1.0, 1.0 and 1.0, respectively, p=0.005). Conclusions: The risk of treatment failure was higher in patients with SCA profile, but only in patients over 18 months. All relapses occurred in children having obtained the complete remission, with no previous radiotherapy. In patients over 18 months, SCA profile should be taken into consideration for therapy stratification as it increases the risk of relapse and this group may require more intensive treatment.